Oral administration of palm oil (elaeis) increases abdominal fat more than oral administration of coconut oil (cocos nucifera) in wistar male rats - Cynthia Sofyanti Sugiharto; I Gusti Made Aman; Ida Sri Iswari (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2018)
Introduction: Coconut oils contain many medium-chained fatty acids (MCFA) which are quickly oxidized to produce more energy than long-chained fatty acids (LCFA) in palm oil which is to be accumulated as body fat. The purpose of this study was to determine that oral administration of palm oil (Elaeis) in wistar male rats increased abdominal subcutaneous fat and visceral fat compared to coconut oil (Cocos nucifera). Methods: An experimental post-test only control group study was conducted using 30 male Wistar rats, 2.5-3 months old, with body weight 130-135 grams, which then treated with distilled water in [Control group (P0)], palm oil [Treatment group 1] (P1)] and coconut oil [Treatment group 2 (P2)] with a dose of 2x0.4 ml daily for 45 days. After treatment, the rat was dissected and the visceral abdominal and subcutaneous fats were weighted. All data were analyzed by One Way ANOVA test. Result: According to post-test analysis, the mean weight of abdominal subcutaneous fat was found at 1.18 ± 0.27 grams, 1.60 ± 0.20 grams, and 0.90 ± 0.36 grams in groups P0, P1 and P2 respectively. The mean visceral fat weight was 0.88 ± 0.45 grams, 1.46 ± 0.34 grams, and 0.69 ± 0.35 grams in groups P0, P1 and P2 respectively. One Way ANOVA test analysis found that there were significant differences in mean weight of visceral fat and abdominal subcutaneous fat between the three groups (p <0.05). Conclusion: It was concluded that, with the same dose and timeframe, the administration of oral palm oil in Wistar male rats has more tendency to increase abdominal fat than coconut oil.